Geology of the Toundoute Region (South Morocco): a window on the Early Jurassic-Cretaceous tectono-sedimentary evolution of the Central High Atlas - Marco Benvenuti; Jacopo Nesi; Mauro Papini; Giacomo Risaliti; Federico Sani; Giovanna Moratti (Journal of Maps)
A new geological map representing the southern leading edge of Central High Atlas (Toundoute, South Morocco) updates the stratigraphic architecture of a Lower Jurassic-Cretaceous succession including marine carbonates and terrestrial clastics. Integrated facies and structural analyses outline a marked syn-tectonic control on depositional patterns since the Early Jurassic, as documented by geological maps of adjacent sectors of the Central High Atlas southern flank recently published on Journal of Maps. This incipient diffuse crustal uplift and denudation attests to a pre-collisional stage in the development of the Central High Atlas mountains.